Global, regional, and national trends in pulmonary arterial hypertension burden, 1990–2021: findings from the global burden of disease study 2021 - Liu, Zhenhao; Mo, Liumei; Cao, Wenjing; Wang, Kui; Gong, Hanxian; Li, Chen; Pan, Wei; He, Jinqing (Frontiers in Public Health, 2025)
ObjectivesPulmonary arterial hypertension (PAH) is a severe and life-threatening condition. This study systematically examines the global epidemiology of PAH, focusing on trends in incidence, mortality, and disability-adjusted life years (DALYs) over the past 32 years to inform evidence-based policy and healthcare strategies.MethodsData from the Global Burden of Disease (GBD) 2021 study was used to analyze PAH incidence, mortality, and DALYs globally, regionally, and nationally from 1990 to 2021. Age-standardized incidence rate (ASIR), death rate (ASMR), disability-adjusted life years rate (ASDR) and estimated annual percentage change (EAPC) were assessed by age, gender, and socio-demographic index (SDI) quintiles. Hierarchical cluster analysis was performed to evaluate the temporal patterns of disease burden changes across GBD regions.ResultsGlobal PAH incident cases increased by 85.6%, from 23,301 in 1990 to 43,251 in 2021. ASIR increased slightly from 0.50 to 0.52 per 100,000 persons (EAPC 0.05%). From 1990 to 2021, PAH-related deaths increased from 14,842 to 22,021, though ASMR decreased (EAPC -0.57%). In 2021, PAH accounted for 642,104 DALYs, with ASDR showing a downward trend (EAPC -1.31%). Regions with low SDI exhibited the highest ASIR, while both ASMR and DALYs decreased across all SDI categories. Southern Sub-Saharan Africa had the highest incidence, while Central Asia saw the largest increases in mortality and DALYs.ConclusionOver the past 32 years, global ASMR and ASDR for PAH have decreased, while ASIR showed a modest increase. Persistent imbalances in treatment and outcomes remain in certain regions. Enhanced prevention and comprehensive management strategies are needed to diminish the global PAH burden and improve health equity.